Particle-in-cell simulations of the alpha and gamma modes in collisional nitrogen capacitive discharges. (9th March 2021) - Kawamura, E; Lieberman, M A; Lichtenberg, A J; Chabert, P
Abstract: We perform one-dimensional (1D) particle-in-cell (PIC) simulations to study the α and γ modes in an intermediate pressure 1.6 Torr, 2.5 cm gap capacitive nitrogen discharge driven at 13.56 MHz with current density amplitudes J 0 = 7 to 150 A m −2 . In the α-mode, ion-induced secondary electron emission has minimal effects on the discharge equilibrium, while in the γ-mode, it is essential for sustaining the discharge. As in a previous study of a comparable argon discharge, [Kawamura et al 2020, J. Vac. Sci. Technol. A 38, 023003], the nitrogen discharge in the α-mode can be described by a 'passive bulk' model in which the ionization is negligible in the central bulk region and is due solely to electron sheath heating. The nitrogen discharge undergoes an α to γ transition in the applied J 0 range, characterized by an increase in density and a decrease in electron temperature, sheath widths and sheath voltages. For the γ-mode, we calculate the scalings of the maximum sheath width s m and the rf sheath voltage amplitude V 1 with J 0 . We compare the PIC results in the α-mode to the passive bulk model (modified for nitrogen), and, in the γ-mode with the expected J 0 - V 1 and s m - V 1 curves. We find good agreement with the simulations in both the α and γ regimes, and the α to γ transition is well predicted by the models.